EMOSI TOKOH UTAMA DALAM NOVEL YORICK KARYA KIRANA KEJORA - Sagita, Dian; Syam, Christanto; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was conducted to know the emotions of the main character in novel Yorick by Kirana Kejora. The goal was to describe the positive and negative emotions towards the attitude of the main character as well as the implementation of this research in learning Indonesian Language in schools. The theory used in this research was B.F. Skinner theory. This research applied descriptive, qualitative, and psychological method. The data source in this study is novel Yorick by Kirana Kejora. In collecting the data, the researcher used documentary study technique. The tool of data collection used in thie research was the researcher herself as a key instrument. In conclusion, the results of the analysis were, (1) positive emotions influence the main character's attitude were 6 emotions of love, and 13 emotions of happiness. (2) Negative emotions influence the main character's attitude were 4 emotions of worry and anxiety, 4 emotions of fear, 5 emotions of anger, and 6 emotions of sadness. (3) Novel Yorick by Kirana Kejora can be used as teaching material in schools because there are values of struggle and moral messages to be applied in achieving ideals and a better future. Keywords: Logical, Main Character, Behavioral Psychology.